2007
DOI: 10.1373/clinchem.2006.079186
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry–Based Hepcidin Measurements in Serum and Urine: Analytical Aspects and Clinical Implications

Abstract: Background: Discovery of the central role of hepcidin in body iron regulation has shed new light on the pathophysiology of iron disorders. Information is lacking on newer analytical approaches to measure hepcidin in serum and urine. Recent reports on the measurement of urine and serum hepcidin by surface-enhanced laserdesorption/ionization time-of-flight mass spectrometry (SELDI-TOF MS) necessitate analytical and clinical evaluation of MS-based methodologies. Methods: We used SELDI-TOF MS, immunocapture, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
210
1
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(238 citation statements)
references
References 28 publications
19
210
1
8
Order By: Relevance
“…Recently, several investigators have indicated the existence of an erythropoiesis-associated humoral factor that negatively regulates hepcidin synthesis, mainly based on animal experiments and in vitro experiments using sera of β-thalassemia patients. [9][10][11][12][13][14] These patients usually show severe microcytic anemia, increased iron stores and ineffective erythropoiesis with relatively low hepcidin production, and a clear inverse correlation was observed between the urinary hepcidin level and levels of both erythropoietin and sTfR. 20 Kemna et al demonstrated that patient sera containing high sTfR levels could suppress hepcidin mRNA expression in human hepatoma cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several investigators have indicated the existence of an erythropoiesis-associated humoral factor that negatively regulates hepcidin synthesis, mainly based on animal experiments and in vitro experiments using sera of β-thalassemia patients. [9][10][11][12][13][14] These patients usually show severe microcytic anemia, increased iron stores and ineffective erythropoiesis with relatively low hepcidin production, and a clear inverse correlation was observed between the urinary hepcidin level and levels of both erythropoietin and sTfR. 20 Kemna et al demonstrated that patient sera containing high sTfR levels could suppress hepcidin mRNA expression in human hepatoma cells.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these signals, the existence of erythropoiesis-associated regulatory factors of hepcidin has been hypothesized. [9][10][11][12] Consistent with this hypothesis, hepcidin expression increased when hematopoiesis in mice was blocked by irradiation or chemotherapeutic agents. However, this increase was not suppressed by erythropoietin administration or anemia caused by phenylhydrazine or phlebotomy, indicating that neither erythropoietin nor anemia per se was the hepcidin regulator.…”
Section: Introductionmentioning
confidence: 84%
“…There are numerous variations and modifications of MS (e.g., HPLC-MS/MS, MALDI-TOF MS, and SELDI-TOF) that have been employed by different laboratories to measure hepcidin levels in biological samples, however, the details of these modifications are beyond the scope of this paper [8][9][10][11]. One of the major benefits of measuring hepcidin by MS methodologies is the ability to distinguish and quantitate the bioactive hepcidin-25 [11].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…A general advantage of MS-based approaches is that it allows the visualisation of different isoforms of the same protein, which are otherwise difficult to distinguish by ELISA-based methods [53,54]. A limitation of antigen profiling is that MS-based assays provide qualitative data, whereas quantification still needs much improvement.…”
Section: Antigen Profiling By Msmentioning
confidence: 99%